Analysis of HbA1c levels in patients with type 2 diabetes: a study at dustira hospital, cimahi - Kusmala, Yudith Y; Wirasiti, Deasy; Sihotang, Shareen A (ACTA Medical Health Sciences, 2025)
The HbA1c test has been recommended by the International Committee and the American Diabetes Association to diagnose and monitor the effectiveness of therapy in patients with diabetes mellitus. Pharmacological therapy for controlling blood sugar levels in patients with type 2 diabetes mellitus may include oral medications, insulin, or a combination of both. This study aimed to compare the average HbA1c levels of patients with type 2 diabetes mellitus using oral antidiabetic drugs (OAD), insulin, or a combination of OAD and insulin. This research utilized an observational analytic method with a cross-sectional design and employed a consecutive sampling technique, analyzing patients' medical records from January 2019 to June 2022 at Dustira Hospital. Bivariate analysis was performed using the Kruskal-Wallis test, followed by the Mann-Whitney test. The study concluded that among the 123 data samples, 41 patients using OAD had an average HbA1c of 11.77%, 41 patients undergoing insulin therapy had an average HbA1c of 9.68%, and 41 patients receiving a combination of OAD and insulin had an average HbA1c of 10.73%. The results indicated a significant difference in the average HbA1c levels between the OAD and insulin treatment groups (p=0.002; < 0.05) and no significant difference between the OAD and OAD-insulin combination groups (p=0.092; > 0.05). Although significant differences in average HbA1c levels were observed between the three types of management, the ideal HbA1c target had not been achieved. This suggests that other factors, such as patient adherence to medication, physical activity patterns, nutritional diet, and the duration of diabetes mellitus, may also play a role in influencing treatment outcomes. DOI : 10.35990/amhs.v4n1.p9-16 REFERENCES World Health Organization (WHO). Use of glycated haemoglobin (HbA1c) in the diagnosis of diabetes mellitus. Diabetes Res Clin Pract. 2011;93:299–309. Available from: https://doi.org/10.1016/j.diabres.2011.03.012 World Health Organization (WHO). Classification of diabetes mellitus. Geneva: WHO; 2019. Kementerian Kesehatan Republik Indonesia (Kemenkes RI). Cegah, cegah, dan cegah: suara dunia perangi diabetes. Jakarta: Kemenkes RI; 2018. Available from: https://www.kemkes.go.id/article/view/18121200001/prevent-prevent-and-prevent-the-voice-of-the-world-fight-diabetes.html International Diabetes Federation (IDF). Diabetes Atlas. 10th ed. Brussels: IDF; 2021. p.6–9. Available from: www.diabetesatlas.org Kementerian Kesehatan Republik Indonesia. Infodatin: Tetap produktif, cegah, dan atasi diabetes melitus. Jakarta: Pusdatin Kemenkes RI; 2020. p.1–10. Dinas Kesehatan Jawa Barat. Jumlah penderita diabetes melitus berdasarkan kabupaten/kota di Jawa Barat. Bandung: Dinkes Jabar; 2020. Available from: https://opendata.jabarprov.go.id/idk/dataset/jumlah-penderita-diabetes-melitus-berdasarkan-kabupatenkota-di-jawa-barat Lestari R. Kendalikan diabetes melalui program Affordability Project. Bandung: Dinkes Jabar; 2022. Available from: https://diskes.jabarprov.go.id/informasi-publik/detail_berita/dWEwYUlUczBLQjJoaFhHUUU5YkpKZz09 Kim HJ, Choi EY, Park EW, Cheong YS, Lee HY, Kim JH. The utility of HbA1c as a diagnostic criterion of diabetes. Korean J Fam Med. 2011;32(7):383. Available from: http://dx.doi.org/10.4082/kjfm.2011.32.7.383 Rakhmat II, Kusmala YY, Handayani DR, Juliastuti H, Nawangsih EN, Wibowo A, et al. Dipeptidyl peptidase-4 (DPP-4) inhibitor and mortality in coronavirus disease 2019 (COVID-19): a systematic review, meta-analysis, and meta-regression. Diabetes Metab Syndr Clin Res Rev. 2021;15:777–82. Available from: https://doi.org/10.1016/j.dsx.2021.03.027 Handayani DR, Juliastuti H, Nawangsih EN, Kusmala YY, Rakhmat II, Wibowo A, et al. Prognostic value of fasting hyperglycemia in patients with COVID-19: diagnostic test accuracy meta-analysis. Obes Med. 2021;23:100333. Available from: https://doi.org/10.1016/j.obmed.2021.100333 Widiasari KR, Wijaya IMK, Suputra PA. Diabetes melitus tipe 2: faktor risiko, diagnosis, dan tatalaksana. Ganesha Med. 2021;1(2):114. Available from: https://doi.org/10.23887/gm.v1i2.40006 Hakim A, Ismunandar H, Wahyuni A, Sangging PRA. Manajemen diabetes melitus: an update. Medula. 2022;12(1):160–5. Arini NMA, Dwipayana IMP. Hubungan kadar HbA1c terhadap terapi obat anti diabetes oral dan kombinasi obat anti diabetes oral–insulin pada penderita diabetes melitus tipe 2 di Poliklinik Diabetes RSUP Sanglah Denpasar tahun 2016. J Med Udayana. 2020;9(9):94–9. Available from: https://doi.org/10.24843/MU.2020.V9.i9.P16 Versita R, Handayani D, Adiningsih R, Oktoviani. Hubungan pola penggunaan obat terhadap lama rawat pada pasien. Ilm Kefarmasian. 2022;7(4):781–8. Available from: https://doi.org/10.37874/ms.v7i4.476 Prasetyani D, Sodikin S. Analisis faktor yang mempengaruhi kejadian diabetes melitus tipe 2. J Kesehat Al-Irsyad. 2017;10(2):5–7. Jamaluddin G, Nalapraya WY. Perbandingan efektivitas insulin, obat antidiabetik oral dan kombinasi terhadap kadar gula darah pada pasien rawat jalan dengan DM tipe 2 di RSUD Al-Ihsan. Medika. 2021:511–6. Putra IWMM, Budyono C, Ekawanti A, Anggoro J. Factors affecting controlled blood sugar levels in patients with type 2 diabetes mellitus at the internal medicine polyclinic at the Regional General Hospital of West Nusa Tenggara Province. J Biol Trop. 2023;23(1):65–72. Available from: https://doi.org/10.29303/jbt.v23i1.4509 Mahfudzoh BS, Yunus M, Ratih SP. Hubungan antara faktor risiko diabetes melitus yang dapat diubah dengan kejadian DM tipe 2 di Puskesmas Janti Kota Malang. Sport Sci Heal. 2019;1(1):59–71. Perkumpulan Endokrinologi Indonesia (Perkeni). Pedoman pengelolaan dan pencegahan diabetes melitus tipe 2 di Indonesia 2021. Jakarta: Perkeni; 2021. Sugandha PU, Lestari AW. Gambaran pengendalian kadar gula darah dan HbA1c pada pasien diabetes melitus tipe 2 yang dirawat di RSUP Sanglah periode Januari–Mei 2014. E-Jurnal Med Udayana. 2015;4(1):1–8. Hirsch IB, Gaudiani LM. Using insulin to treat poorly controlled type 2 diabetes in 2020. JAMA Insight. 2020:5–6. Available from: https://doi.org/10.1001/jama.2020.1303 Udayani NNW, Ratnasari NLAM, Cahyaningsih E, Wardani IGAAK. Evaluasi efek samping penggunaan kombinasi insulin pada pasien rawat jalan diabetes melitus tipe 2 di salah satu rumah sakit kota Denpasar. J Med Udayana. 2021;7(2):112–7. Available from: https://doi.org/10.36733/medicamento.v7i2.2178 Dujunco MM, Gorriceta JH, Dampil OA, Mirasol R. Initiate study: insulin versus oral hypoglycemic agent as initial therapy for newly diagnosed diabetes mellitus type 2: a systematic review and meta-analysis. J ASEAN Fed Endocr Soc. 2014;29(2):172–8. Available from: http://dx.doi.org/10.15605/jafes.029.02.11 Zulkarnain NF, Adawiyah R. Kepatuhan penggunaan obat oral anti-diabetes pada pasien diabetes melitus tipe 2 di puskesmas wilayah Kota Malang dengan model The Medication Adherence Report Scale-5. Sitawa J Farm Sains Obat Tradis. 2025;4(1):1–8. Hasanah U, Kurniawati D, Mustaqimah M, Yuwindry I. Hubungan kepatuhan pasien diabetes dalam mengkonsumsi obat antidiabetes oral terhadap kadar gula darah puasa di RSUD Ulin Banjarmasin. J Surya Med [Internet]. 2024;10(2):64–8. Available from: https://doi.org/10.33084/jsm.v10i2.7725 Alsaidan AA, Alsaidan OA, Mallhi TH, Khan YH, Alzarea AI, Alanazi AS. Assessment of adherence to insulin injections among diabetic patients on basal-bolus regimen in primary and secondary healthcare centers in Al-Jouf Region of Saudi Arabia: a descriptive analysis. J Clin Med. 2023;12(10):3474. Available from: https://doi.org/10.3390/jcm12103474 Osborn C, Gonzales J. Measuring insulin adherence among adults with type 2 diabetes. J Behav Med [Internet]. 2016;39(4):633–41. Available from: https://doi.org/10.1007/s10865-016-759-1